Monitoring in the Academic Work Organization discipline: Articulating theory and practice in the Geography Degree EaD course UAB / UFAL / A monitoria na disciplina Organização do Trabalho Acadêmico: Articulando teoria e prática no curso Geografia Licenciatura EaD UAB/UFAL - Michelle Emanuelle Silva; Ricardo Santos de Almeida; Cirlene Jeane Santos e Santos (Universidade Estadual de Alagoas, 2016)
The practice of academic research requires a systematic analysis of the study area - geography to understand the object of science studied, the geographic space. Monitoring in higher education is essential to the academic development of future teacher. It is from this that the monitor has its first contact with the classroom in practice, but without classroom lectures. It is intended to study and understand the practices occurring in monitoring the course of the Academic Labor Organization highlighting how the teaching was conducted by subdividing into specific units, among which we emphasize: Teacher also search: Learning and seize on the Geographic Space which we operate; Read, Interpret and Analyze: Understand the role and importance of research; Research Roadmap: Which way to go? In this sense, we intend to examine how the practice of academic research acts as the driving force for the development of academic works although there are specific to the development and preparation of academic work spaces for discussions. We also analyzed the motivation factor for undergraduates interested is by conducting surveys do not performing academically so only as preparation for the final completion of course work. We can say that from this discipline future teachers understand the importance of discipline Organização do Trabalho Acadêmico for its development throughout the academic life and also learned how the rules of the Associação Brasileira de Normas Técnicas (ABNT) work and how transform the appearance of a job highlighting theoretical, methodological work for the reader aspects